SYMBOLIC RESISTANCE OF ACEHNESE STUDENTS AGAINST NATIONAL NARCOTICS AGENCY HEGEMONY ON DRUG ERADICATION - Mohd Nasir; Muhaini Muhaini; Muhammad Mukhlis (JURNAL TARBIYAH, 2019)
This study will describe the form of symbolic resistance of Acehnese students to drug eradication and photograph the forms of hegemony represented by the NNA Aceh in eradicating drugs for students in Aceh using the symbolic resistance theory of James C. Scott and Gramsci's hegemony. This research explored information through informants by conducting in-dept interviews, participant observation and documentation. This study found that the presence of students carrying symbolic resistance to drug eradication carried out by the National Narcotics Agency in the form of feeling uncomfortable, rejection body language, pouting officers and looking for excuses when counseling was conducted. This symbolic resistance emerged as a reaction to hegemony in various forms, namely dissemination, anti-drug volunteers, monday national flag ceremony, urine tests, seminar, DAPEICP curriculum and MoU.